2023
DOI: 10.3390/ma16103619
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Influence of Wire-Saw Wear on Cutting Force and Silicon Wafer Surface

Abstract: Hard and brittle materials such as monocrystalline silicon still occupy an important position in the semiconductor industry, but hard and brittle materials are difficult to process because of their physical properties. Fixed-diamond abrasive wire-saw cutting is the most widely used method for slicing hard and brittle materials. The diamond abrasive particles on the wire saw wear to a certain extent, which affects the cutting force and wafer surface quality in the cutting process. In this experiment, keeping al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…On the one hand, Si 3 N 4 ceramics are prone to brittle fracture when cutting, and the discontinuous chips result in brittle pits on the machined surface. On the other hand, due to the vibration of the saw wire in cutting [ 9 , 17 ] and the uneven size of the abrasive grains on the diamond saw wire surface [ 8 ], then the cut depths of abrasive grains are inconsistent at different positions of the wire surface, which results in an uneven surface. Numerous studies have shown that when the depth of abrasive cutting of hard-brittle materials is below the critical cutting depth, the material can be removed in a ductile manner to obtain high-quality machined surfaces [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, Si 3 N 4 ceramics are prone to brittle fracture when cutting, and the discontinuous chips result in brittle pits on the machined surface. On the other hand, due to the vibration of the saw wire in cutting [ 9 , 17 ] and the uneven size of the abrasive grains on the diamond saw wire surface [ 8 ], then the cut depths of abrasive grains are inconsistent at different positions of the wire surface, which results in an uneven surface. Numerous studies have shown that when the depth of abrasive cutting of hard-brittle materials is below the critical cutting depth, the material can be removed in a ductile manner to obtain high-quality machined surfaces [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, laser cutting causes relatively deep thermal damage layers on the surface and subsurface of the ceramic substrate and slice warpage. In recent years, diamond wire saw slicing technology has been widely used for slicing hard-brittle materials such as photovoltaic and semiconductor silicon crystals [ 8 , 9 ], silicon carbide crystals [ 10 ], sapphire [ 11 , 12 ], quartz [ 13 ] and magnetic materials [ 14 ] due to the advantages of its high sawing performance and small kerf loss. For the slicing processing of Si 3 N 4 ceramics, the diamond wire saw slicing technology has great application potential.…”
Section: Introductionmentioning
confidence: 99%
“…In the experiment, a wire saw cuts many wafers. According to the research in [ 31 ], the wear state of abrasive particles can affect the cutting force in the experiment, and abrasive wear is not considered in the simulation. In the early stage of abrasive wear, there is a small change in cutting force, while in the stable wear stage, cutting force decreases; moreover, in the later stage of wear, there is a significant change in cutting force.…”
Section: Simulation and Experimentsmentioning
confidence: 99%